PHYSICAL ACTIVITY AS FACTOR IN COPING WITH STRESS AMONG WORKING STUDENTS - Vranic, Natasa; Bozovic, Maja; Tosic Bakovic, Milica; Rodic, Branka (Sport - nauka i praksa, 2026)
Stress is one of the major challenges students face during their education, and it is particularly pronounced among those who study and work simultaneously. Chronic stress can negatively affect work performance, focus, professional efficiency, and academic achievement. Physical activity is recognized in literature as an important protective factor that contributes to the preservation of psychophysical health and may mitigate the negative effects of stress. This study aimed to examine the association between physical activity and perceived stress among working students, with a particular focus on the frequency and type of physical activity. The study included 196 participants who were simultaneously students and employed. Perceived stress was assessed using the Perceived Stress Scale (PSS-10), and the data were analyzed using descriptive statistics, correlation analysis, the independent-samples t-test, and one-way analysis of variance (ANOVA). The results indicate that most working students are affected by a moderate level of stress, with the most common sources being the balancing of academic and work obligations and a lack of free time. Gender-based analyses showed that women report higher average levels of stress compared to men. Students who engage in regular physical activity exhibit significantly lower levels of perceived stress compared to those who exercise rarely or not at all, with group-based forms of physical activity being associated with lower stress levels. The findings highlight the importance of physical activity as a valuable resource for maintaining the mental health of working students and underscore the need to promote healthy lifestyle behaviors within the student population.
Keywords: physical activity; stress; students; mental health